Biomimetic three-dimensional nanocrystalline hydroxyapatite and magnetically synthesized single-walled carbon nanotube chitosan nanocomposite for bone regeneration - Im O (Dove Medical Press, 2012)
Owen Im1, Jian Li2, Mian Wang2, Lijie Grace Zhang2,3, Michael Keidar2,31Department of Biomedical Engineering, Duke University, Durham, NC; 2Department of Mechanical and Aerospace Engineering, 3Institute for Biomedical Engineering and Institute for Nanotechnology, The George Washington University, Washington, DC, USABackground: Many shortcomings exist in the traditional methods of treating bone defects, such as donor tissue shortages for autografts and disease transmission for allografts. The objective of this study was to design a novel three-dimensional nanostructured bone substitute based on magnetically synthesized single-walled carbon nanotubes (SWCNT), biomimetic hydrothermally treated nanocrystalline hydroxyapatite, and a biocompatible hydrogel (chitosan). Both nanocrystalline hydroxyapatite and SWCNT have a biomimetic nanostructure, excellent osteoconductivity, and high potential to improve the load-bearing capacity of hydrogels.Methods: Specifically, three-dimensional porous chitosan scaffolds with different concentrations of nanocrystalline hydroxyapatite and SWCNT were created to support the growth of human osteoblasts (bone-forming cells) using a lyophilization procedure. Two types of SWCNT were synthesized in an arc discharge with a magnetic field (B-SWCNT) and without a magnetic field (N-SWCNT) for improving bone regeneration.Results: Nanocomposites containing magnetically synthesized B-SWCNT had superior cytocompatibility properties when compared with nonmagnetically synthesized N-SWCNT. B-SWCNT have much smaller diameters and are twice as long as their nonmagnetically prepared counterparts, indicating that the dimensions of carbon nanotubes can have a substantial effect on osteoblast attachment.Conclusion: This study demonstrated that a chitosan nanocomposite with both B-SWCNT and 20% nanocrystalline hydroxyapatite could achieve a higher osteoblast density when compared with the other experimental groups, thus making this nanocomposite promising for further exploration for bone regeneration.Keywords: nanomaterials, single-walled carbon nanotube, nanocrystalline hydroxyapatite, chitosan, bone regeneration, biomimetic